PENERAPAN MODEL COOPERATIVE LEARNING TIPE STAD DENGAN BERBANTUAN APLIKASI WORDWALL PADA PELAJARAN IPS SISWA KELAS IV SD NEGERI 06 LUBUKLINGGAU - Anisa, Anisa Miftahul Jannah; Dodik Mulyono; Asep Sukenda Egok (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to complete the social studies learning outcomes of fourth grade students at SD Negeri 06 Lubuklinggau using the STAD type cooperative learning model with the help of the wordwall application in social studies lessons. This type of research uses a quasi-experimental method, the design used is a one-group pretest-posttest design. The place and time of the research was carried out at SD Negeri 06 Lubuklinggau, West Lubuklinggau I District, Lubuklinggau City with the research time in the even semester. The research population was 27 class IV students at SD Negeri 06 Lubuklinggau, the research sample used a total sampling technique. Pre-test and post-test data collection techniques using 7 descriptive questions. From the results of data analysis using the Z test with a significant level of α = 0.05, it was found that Zcount ˃ Ztabel (6.31 ˃ 1.64), so it can be concluded that there are social studies learning outcomes for class IV students at SD Negeri 06 Lubuklinggau by implementing the cooperative learning model STAD type with the help of the wordwall application.